Visualize it!

Algebra Level 5

{ x 2 + y 2 + x y = 1 x 2 + z 2 + x z = 3 z 2 + y 2 + z y = 4 \large{\begin{cases} x^2+y^2+xy=1 \\ x^2 + z^2 + xz = 3 \\ z^2 +y^2 + zy = 4 \end{cases} }

If x , y x,y and z z are positive real numbers satisfying the system of equations above, find ( x + y + z ) 2 (x+y+z)^2 .


The answer is 7.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Choi Chakfung
Mar 7, 2016

Where did you require cosine formula?

Anik Mandal - 5 years, 3 months ago

Log in to reply

just use the cosine formula to find out the length of side of the triangle.

choi chakfung - 5 years, 3 months ago

Log in to reply

Oh yeah! Thanks!Great solution though!

Anik Mandal - 5 years, 3 months ago

this is called a great solution !!

Mrigank Krishan - 5 years, 3 months ago
Aditya Dhawan
Apr 2, 2016

{ x 2 + y 2 + x y = 1 ( A ) x 2 + z 2 + x z = 3 ( B ) z 2 + y 2 + z y = 4 ( C ) ( B ) ( A ) a n d ( C A ) y i e l d : ( z y ) ( x + y + z ) = 2 ( a ) ( z x ) ( x + y + z ) = 3 ( b ) D i v i d i n g ( b ) b y ( a ) ( z x ) ( z y ) = 3 / 2 w h i c h f u r t h e r s i m p l i f i e s t o z = 3 y 2 x N o w p l u g g i n g t h i s v a l u e b a c k i n t o ( a ) w e o b t a i n : 4 y 2 5 x y + x 2 = 1 ( c ) N o w ( c ) ( A ) 3 y 2 = 6 x y y = 2 x N o w z = 6 x 2 x = 4 x P l u g g i n g i n t o ( b ) x 2 = 1 7 x = 1 7 , y = 2 7 , z = 4 7 C h e c k i n g i f o u r s o l u t i o n i s v a l i d , 1 + 4 + 2 7 = 1 ( A ) 1 + 16 + 4 7 = 3 ( B ) 4 + 16 + 8 7 = 4 ( C ) T h u s ( x + y + z ) 2 = ( 49 x 2 ) = 7 { \begin{cases} x^{ 2 }+y^{ 2 }+xy=1(A) \\ x^{ 2 }+z^{ 2 }+xz=3(B) \\ z^{ 2 }+y^{ 2 }+zy=4(C) \end{cases} }\\ (B)-(A)\quad and\quad (C-A)\quad yield:\\ (z-y)(x+y+z)=2\quad (a)\\ (z-x)(x+y+z)=3(b)\\ \\ Dividing\quad (b)\quad by\quad (a)\quad \\ \frac { (z-x) }{ (z-y) } =\quad 3/2\quad \\ which\quad further\quad simplifies\quad to\quad \boxed { z=3y-2x } \\ Now\quad plugging\quad this\quad value\quad back\quad into\quad (a)\quad we\quad obtain:\\ 4{ y }^{ 2 }-5xy+{ x }^{ 2 }=1(c)\\ Now\quad (c)-(A)\Longrightarrow 3{ y }^{ 2 }=6xy\Longrightarrow \boxed { y=2x } \\ Now\quad z=\quad 6x-2x=\boxed { 4x } \\ Plugging\quad into\quad (b)\\ \boxed { { x }^{ 2 }=\frac { 1 }{ 7 } } \Longrightarrow x=\frac { 1 }{ \sqrt { 7 } } ,y=\frac { 2 }{ \sqrt { 7 } } ,z=\frac { 4 }{ \sqrt { 7 } } \\ Checking\quad if\quad our\quad solution\quad is\quad valid,\\ { \frac { 1+4+2 }{ 7 } }=1(A)\\ \frac { 1+16+4 }{ 7 } =3(B)\\ \frac { 4+16+8 }{ 7 } =4(C)\\ Thus\quad ({ x+y+z) }^{ 2 }=(49{ x }^{ 2 })=\boxed { 7 } \\ \\ \\ \\

Moderator note:

When manipulating equations, we have to check if we introduced extraneous solutions.

For example, there is no solution to x 2 + x = 3 , x 2 = 2 x^2 + x = 3, x^2 = 2 , even though we can subtract the equations to get x = 1 x = 1 .

As such, you will need to verify that the final value which you calculated is indeed a possible solution to the original system of equations.

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...